1995
DOI: 10.3168/jds.s0022-0302(95)76749-2
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis in Samples of Quarter Milk with Varying Somatic Cell Counts. 1. Comparison of Some Indicators of Endogenous Proteolysis in Milk

Abstract: Eighty-six samples of quarter milk from 31 cows, the mean SCC of which exceeded 400,000 cells/ml, were analyzed for SCC, chloride content, pH, clotting time, total N, soluble N, casein N, proteose-peptone content, plasmin activity, and amount of free NH2 groups, parameters that are related to the udder health condition and to the deterioration of the protein quality. Analysis of the milk from each quarter separately improved the correlations considerably compared with analyses of samples from all 4 quarters mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
73
1
7

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 21 publications
11
73
1
7
Order By: Relevance
“…Haenlein et al (1973) present significantly lower contents of casein, a s1 -CN, b-CN, b-lactoglobulin, a-lactalbumin and whey proteins, and a lower casein number with increasing degrees of subclinical mastitis and SCC. A study by Le Roux et al (1995) showed that protein composition starts to change even at low levels of SCC (.250 000 cells/ml) in udder quarter milk. In this study, protein composition was also influenced in milk from affected udder quarters in Group 2, for which the udder quarter mean SCC was 285 000 cells/ml.…”
Section: Forsbä Ck Lindmark-må Nsson André N and Svennersten-sjaunjamentioning
confidence: 99%
“…Haenlein et al (1973) present significantly lower contents of casein, a s1 -CN, b-CN, b-lactoglobulin, a-lactalbumin and whey proteins, and a lower casein number with increasing degrees of subclinical mastitis and SCC. A study by Le Roux et al (1995) showed that protein composition starts to change even at low levels of SCC (.250 000 cells/ml) in udder quarter milk. In this study, protein composition was also influenced in milk from affected udder quarters in Group 2, for which the udder quarter mean SCC was 285 000 cells/ml.…”
Section: Forsbä Ck Lindmark-må Nsson André N and Svennersten-sjaunjamentioning
confidence: 99%
“…These modifications are in relation to the level of SCC and are linked to the germ present in the udder, particularly in cases of clinical mastitis [19,47,48]. The threshold of SCC for a normal milk is variable in function of the authors but more often than not over 10 5 cells/mL [19,41,69]. The decrease of synthesis in mammary epithelial cells (indicated by a decrease in lactose content) and the proteolysis (indicated by an increase in proteose-peptone content and plasmin activity) are statistically significant for low SCC (Tab.…”
Section: The Relationship Between Scc and Milk Composition In Quartermentioning
confidence: 99%
“…In UHT milk, plasmin seems implicated in gelation during storage [35]. Milk obtained from mastitic or high SCC quarter milk contains high concentrations of plasmin [41]. Within the plasmin system, activators and inhibitors control plasmin activity.…”
Section: An Increase In Proteolytic Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…On a more fundamental basis, mastitis involves three phenomena: a decrease of synthesis [22,24], an increase in permeability of the blood-milk barrier [24,28] and an increase in proteolytic activity in milk [16,24]. In the case of a lipopolysaccharide (LPS) infusion, plasmin and somatic cell proteases are the main origins of endogenous proteolysis [26].…”
Section: F Moussaoui Et Almentioning
confidence: 99%